Exploring the Evolutionary History and Phylodynamics of Human Immunodeficiency Virus Type 1 Outbreak From Unnao, India Using Phylogenetic Approach - Patil, Ajit; Patil, Sandip; Rao, Amrita; Gadhe, Sharda; Kurle, Swarali; Panda, Samiran (Frontiers in Microbiology, 2022)
Certain rural and semi-urban settings in the Unnao district, Uttar Pradesh, India observed an unprecedented increase in the detection of HIV cases during July 2017. Subsequent investigations through health camps and a follow-up case-control study attributed the outbreak to the unsafe injection exposures during treatment. In this study we have undertaken the secondary analysis to understand the phylogenetic aspects of outbreak associated HIV-1 sequences along with origin as well as phylodynamics of the these sequences. The initial phylogenetic analysis indicated separate monophyletic grouping and there was no mixing of outbreak associated sequences with sequences from other parts of India. Transmission network analysis using distance based as well as non-distance based methods revealed the existence of transmission clusters within the monophyletic Unnao clade .The median time to the most recent common ancestor (tMRCA) for sequences from Unnao using pol gene region was observed to be 2011.87 [95% Highest Posterior Density (HPD): 2010.09 – 2013.53], while the estimates using envelope (env) gene region sequences traced the tMRCA to 2010.33 (95% HPD: 2007.76 – 2012.99). Phylodynamics estimates demonstrated that the pace of this local epidemic has slowed down in recent times prior to the time of sampling, but was certainly on an upward track since its inception till 2014.